CSRC’s supervision and corporate investment efficiency—based on the random inspection - Jinyang Liu (China Journal of Accounting Studies, 2023)
ABSTRACTThe random inspection is an important innovation of CSRC’s regulatory initiatives. Using this quasi-natural experiment conducted by the CSRC, we examine the impact of the random inspection on corporate investment efficiency. The result shows that after the listed firms are inspected, the investment efficiency is significantly improved. Further analysis shows that the improvement of accounting information quality and corporate governance are two important channels through which random inspection affects corporate investment efficiency. Cross-sectional analysis finds that the effect is more pronounced in the group with low internal control and poor legal environment. Lastly, we find that secondary random inspection can significantly strengthen the positive association between random inspection and corporate investment efficiency. The conclusions support the positive significance of CSRC’s supervision.